Rare earth modified aluminum strip foil for power battery and production process of rare earth modified aluminum strip foil

By using rare earth modified aluminum tape foil in power batteries and its optimized production process, the problems of insufficient conductivity, low mechanical properties and easy corrosion of traditional aluminum tape foils are solved, and higher conductivity, tensile strength and longer battery cycle life are achieved.

CN119753442APending Publication Date: 2025-04-04INNER MONGOLIA LIANSHENG NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411955914.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional aluminum tape foils have problems such as insufficient conductivity, low mechanical properties and easy corrosion in power batteries, which affect the battery's energy conversion efficiency, mechanical stability and service life.

Method used

Rare earth modified aluminum tape foil and its production process are adopted, and the grain structure and surface protective layer of aluminum tape foil are optimized by adding rare earth elements and alloy elements to the aluminum tape foil, such as smelting, casting, hot rolling, annealing and surface passivation.

Benefits of technology

It significantly improves the conductivity and tensile strength of aluminum tape foil, extends the cycle life of the battery and improves safety, while ensuring the stability and consistency of material performance, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a rare earth modified aluminum strip foil for a power battery and a production process of the rare earth modified aluminum strip foil. The aluminum strip foil consists of the following chemical components in percentage by mass: 0.03-0.2% of Si; 0.01% to 0.1% of Cu; 0.02% to 0.15% of Mn; 0.01% to 0.1% of Mg; 0.05%-0.3% of rare earth elements; and the balance of Al and inevitable impurities. The production process comprises the following steps: S1, smelting; s2, cast rolling; s3, the cast ingot is subjected to heat preservation for 12-24 hours at the temperature of 450-480 DEG C, and air cooling is conducted after furnace cooling is conducted to 200 DEG C or below; s4, hot rolling; s5, annealing is conducted for 2-4 hours at the temperature of 280-320 DEG C; s6, cold rolling; s7, annealing is conducted for 2-6 hours at the temperature of 220-280 DEG C; and S8, passivating treatment is conducted. The aluminum strip foil prepared by the preparation process disclosed by the invention is uniform in grain size, high in conductivity, excellent in mechanical property and excellent in corrosion resistance, is suitable for a current collector of a power battery with high energy density and long service life, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a production process of aluminum foil, and more specifically to a rare earth modified aluminum foil for power batteries and a production process thereof. Background Art

[0002] With the continuous growth of global energy demand and the gradual enhancement of environmental protection awareness, the development of new energy technologies has received widespread attention. Among them, power batteries are the core components of new energy vehicles, and their performance directly affects the range, charging speed and safety of electric vehicles. One of the key components of power batteries is the electrode material, and aluminum foil, as the current collector of the electrode material, plays an important role in improving battery performance.

[0003] At present, traditional power battery aluminum foil is usually made of high-purity aluminum or aluminum alloy, and is mainly used as the current collector of the positive electrode material. Aluminum foil in power batteries mainly undertakes the functions of conducting current, supporting active materials, and improving the overall conductivity of the battery. However, there are still some technical bottlenecks in the practical application of traditional aluminum foil, including:

[0004] (1) Although the conductivity of traditional aluminum foil is relatively high, due to the limited conductivity of aluminum itself, the internal resistance of the battery may increase significantly during high-rate discharge or high-power output, resulting in increased energy loss and affecting the overall energy conversion efficiency of the battery.

[0005] (2) The volume of power batteries changes during the charging and discharging process due to the insertion and extraction of lithium ions, which places higher requirements on the mechanical properties of aluminum foil. Traditional aluminum foil has low strength and toughness, and is prone to deformation or cracking during long-term cycles, affecting the stability of the electrode.

[0006] (3) The working environment of power batteries is complex. Aluminum foil is exposed to strong acidic or alkaline electrolytes for a long time, which is prone to corrosion, resulting in a decrease in the conductivity of the current collector, thus affecting the service life and safety of the battery.

[0007] Based on the above reasons, there is an urgent need to optimize aluminum foil. Summary of the invention

[0008] In order to solve the deficiencies of the prior art, the present invention provides a rare earth modified aluminum foil for power batteries and a production process thereof. The specific scheme is as follows:

[0009] A production process of rare earth modified aluminum foil for power batteries, the production process comprising the following steps:

[0010] S1. Smelting: Smelt aluminum ingots at 730-750°C, add rare earth elements and alloy elements silicon, copper, manganese and magnesium to the melt; stir for 3-5 minutes after adding; after smelting, perform argon refining to remove oxides and gas inclusions;

[0011] S2. Casting: semi-continuous casting or continuous casting and rolling at 710-730°C; controlling the cooling rate to 1.5-3.0°C / s, and controlling the grain size to ≤50μm by using a grain refiner;

[0012] S3, homogenization heat treatment: the ingot is kept at 450-480℃ for 12-24 hours, furnace cooled to below 200℃ and then air cooled;

[0013] S4, hot rolling: hot rolling is carried out at 350-450°C, the single-pass reduction rate is 30%-50%, and the final rolling thickness is 5-8mm;

[0014] S5, intermediate annealing: annealing at 280-320°C for 2-4 hours, followed by slow cooling to room temperature;

[0015] S6, cold rolling: cold rolling the intermediate annealed plate to a target thickness of 20 to 50 μm, with a cold rolling pass reduction of 10% to 20%;

[0016] S7, final annealing: annealing at 220-280°C for 2-6 hours to improve material properties;

[0017] S8. Surface treatment: The surface of the aluminum foil is passivated using a rare earth passivation solution.

[0018] Furthermore, the rare earth element is added in the form of Al-RE master alloy, and the amount of the rare earth element added is 0.05% to 0.3% of the total weight of the melt.

[0019] Furthermore, the rare earth element is one of La, Ce, Nd or Y, or a combination of several of them.

[0020] Furthermore, argon or nitrogen is used for stirring during the smelting process, and the stirring speed is 60 to 100 revolutions per minute.

[0021] Furthermore, the grain refiner is preferably TiB2, and its addition amount is 0.01% to 0.05% of the total weight of the melt.

[0022] Furthermore, the parameters of the S8 surface treatment are as follows:

[0023] Formula of rare earth passivation solution: rare earth salt: 0.1-0.5 mol / L cerium nitrate or lanthanum nitrate or a mixed solution of the two; passivation treatment conditions: temperature: 25-40℃; time: 10-20 minutes; passivation method: immerse the aluminum foil completely in the passivation solution and stir the solution slightly regularly; post-passivation treatment: rinse the surface of the aluminum foil with deionized water for 3-5 minutes to remove the residual passivation solution; dry in hot air or vacuum drying equipment at 50-70℃ to ensure that the passivation film is uniform and stable.

[0024] Furthermore, the microcirculation flow of the passivation liquid is maintained, and the liquid flow rate is 0.5 to 1.5 m / s.

[0025] The invention discloses an aluminum foil prepared by a production process of a rare earth modified aluminum foil for a power battery. The aluminum foil comprises the following chemical components in percentage by mass: Si: 0.03% to 0.2%; Cu: 0.01% to 0.1%; Mn: 0.02% to 0.15%; Mg: 0.01% to 0.1%; rare earth elements: 0.05% to 0.3%; the remainder is Al and unavoidable impurities.

[0026] Beneficial effects:

[0027] The present invention provides a rare earth modified aluminum foil for power batteries and a production process thereof, which has the following beneficial effects compared with the prior art:

[0028] (1) Through the introduction of rare earth elements and optimized production processes, the conductivity of aluminum foil reaches 62% to 65% IACS, which is significantly higher than traditional aluminum foil materials, helping to reduce the internal resistance of power batteries and improve energy efficiency. Rare earth elements are used to refine grains and adjust the ratio of alloy elements, so that the tensile strength of aluminum foil reaches 120 to 130 MPa and the elongation reaches more than 10%, meeting the mechanical performance requirements of power batteries during assembly and use, and reducing the risk of failure of current collectors due to fatigue or deformation.

[0029] (2) During the surface treatment stage, a rare earth oxide protective film is formed on the surface of the aluminum foil using a rare earth passivation solution, so that the corrosion depth of the aluminum foil is ≤5μm after being immersed in a 1M LiPF6 / EC+DMC electrolyte for 48 hours, effectively improving the cycle life and safety of the power battery.

[0030] (3) The production process of the present invention adopts strictly controlled parameters and optimized design steps from smelting to surface treatment, which ensures the stability and consistency of the performance of the aluminum foil, is suitable for large-scale continuous production, and meets the comprehensive requirements of material performance and cost in the field of power batteries. DETAILED DESCRIPTION

[0031] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0032] Embodiment 1:

[0033] S1 Smelting:

[0034] Raw material preparation: aluminum ingot purity above 99.7%; prefabricated Al-La master alloy (rare earth lanthanum content 30%); high-purity silicon, copper, manganese and magnesium.

[0035] Melting temperature: 740℃;

[0036] Ingredients: Add the following alloying elements in percentage by mass to 100 kg of aluminum melt:

[0037] Rare earth elements (La): 0.1%;

[0038] Silicon (Si): 0.08%;

[0039] Copper (Cu): 0.03%;

[0040] Manganese (Mn): 0.05%;

[0041] Magnesium (Mg): 0.02%;

[0042] Stirring conditions: argon stirring, stirring speed of 80 rpm, stirring time of 4 min;

[0043] Refining: Add argon gas for 10 minutes to remove oxide inclusions;

[0044] S2 Casting:

[0045] Casting temperature: 720℃;

[0046] Cooling conditions: Use soft water cooling, cooling rate 2.5℃ / s;

[0047] Grain refiner: TiB2, added in an amount of 0.02% of the total weight of the melt;

[0048] Casting method: semi-continuous casting is adopted, and the ingot grain size is controlled at 30-40μm;

[0049] S3 billet homogenization heat treatment:

[0050] Heat treatment temperature: 470℃;

[0051] Insulation time: 16 hours;

[0052] Cooling method: furnace cooling to 150℃, then taking out and air cooling;

[0053] S4 Hot Rolled:

[0054] Hot rolling starting temperature: 430℃;

[0055] Single pass reduction rate: 40%;

[0056] Final thickness: 6mm;

[0057] S5 intermediate annealing:

[0058] Temperature: 300℃;

[0059] Keep warm time: 3 hours;

[0060] Cooling method: Slowly cool to room temperature;

[0061] S6 Cold Rolled:

[0062] Cold rolling pass reduction rate: 15%;

[0063] Final thickness: 40 μm;

[0064] S7 final annealing:

[0065] Annealing temperature: 240℃;

[0066] Keep warm time: 4 hours;

[0067] Cooling method: natural cooling;

[0068] S8 Surface Treatment:

[0069] Cleaning: Soak in 5% nitric acid solution at 50°C for 2 minutes, then rinse with deionized water for 5 minutes and dry with hot air;

[0070] Passivation: Use 0.3 mol / L lanthanum nitrate (La(NO3)3) solution, soak at 35°C for 15 minutes, while maintaining microcirculation of the passivation solution, with a flow rate of 1m / s;

[0071] Rinse: Rinse with deionized water for 3 minutes;

[0072] Drying: Use hot air drying equipment at 60℃ for quick drying;

[0073] result:

[0074] The aluminum foil produced has uniform grain size, conductivity of 63% IACS, tensile strength of 125 MPa, elongation of 12%, and corrosion depth of only 4.5 μm after immersion in electrolyte for 48 hours.

[0075] Example 2: Preparation process of aluminum foil containing lanthanum (La) and neodymium (Nd) as rare earth elements

[0076] S1 Smelting:

[0077] Raw material preparation: aluminum ingot with a purity of 99.8%; prefabricated Al-La-Nd master alloy (rare earth La content 20%, Nd content 10%); high-purity silicon, copper, manganese, and magnesium;

[0078] Melting temperature: 745℃;

[0079] Ingredients: Add the following alloying elements in the following mass percentages to 200 kg of aluminum melt:

[0080] Rare earth elements (La+Nd): 0.2%, of which La accounts for 0.15% and Nd accounts for 0.05%;

[0081] Silicon (Si): 0.1%;

[0082] Copper (Cu): 0.04%;

[0083] Manganese (Mn): 0.08%;

[0084] Magnesium (Mg): 0.03%;

[0085] Stirring conditions: nitrogen stirring, stirring speed of 70 rpm, stirring time of 5 minutes;

[0086] Refining: Nitrogen was introduced for refining for 15 minutes;

[0087] S2 Casting:

[0088] Casting temperature: 725℃;

[0089] Cooling conditions: soft water cooling, cooling rate 2.0℃ / s;

[0090] Grain refiner: TiB2, added in an amount of 0.03% of the total weight of the melt;

[0091] Casting method: Continuous casting and rolling are adopted, and the ingot grain size is controlled at 20-30μm;

[0092] S3 billet homogenization heat treatment:

[0093] Heat treatment temperature: 460℃;

[0094] Insulation time: 18 hours;

[0095] Cooling method: Furnace cooling to 200℃ and then air cooling;

[0096] S4 Hot Rolled:

[0097] Hot rolling starting temperature: 420℃;

[0098] Single pass reduction rate: 35%;

[0099] Final thickness: 7mm;

[0100] S5 intermediate annealing:

[0101] Temperature: 310℃;

[0102] Keep warm time: 4 hours;

[0103] Cooling method: furnace cooled to room temperature;

[0104] S6 Cold Rolled:

[0105] Cold rolling pass reduction rate: 18%;

[0106] Final thickness: 30 μm;

[0107] S7 final annealing:

[0108] Annealing temperature: 250℃;

[0109] Keep warm time: 5 hours;

[0110] Cooling method: slow cooling;

[0111] S8 Surface Treatment:

[0112] Cleaning: Soak in 45°C, 5% phosphoric acid solution for 1.5 minutes, rinse with deionized water for 4 minutes, and vacuum dry;

[0113] Passivation: Use 0.25 mol / L mixed solution of lanthanum nitrate and neodymium nitrate, soak at 30°C for 20 minutes, stirring at a flow rate of 0.8 m / s;

[0114] Rinse: Rinse with deionized water for 3 minutes;

[0115] Drying: vacuum drying, temperature 60℃;

[0116] result:

[0117] The conductivity of the aluminum foil prepared was 65% IACS, the tensile strength was 130 MPa, the elongation was 11%, and the corrosion depth was 4.2 μm after being immersed in the electrolyte for 48 hours.

[0118] Example 3: Preparation process of aluminum foil containing yttrium (Y) as rare earth element

[0119] S1 Smelting:

[0120] Raw material preparation: aluminum ingot purity 99.7%; prefabricated Al-Y master alloy (rare earth Y content 30%); high-purity silicon, copper, manganese, and magnesium;

[0121] Melting temperature: 730℃;

[0122] Ingredients: Add the following alloying elements in percentage by mass to 50 kg of aluminum melt:

[0123] Rare earth elements (Y): 0.15%;

[0124] Silicon (Si): 0.05%;

[0125] Copper (Cu): 0.02%;

[0126] Manganese (Mn): 0.06%;

[0127] Magnesium (Mg): 0.02%;

[0128] Stirring conditions: argon stirring, stirring speed of 90 rpm, stirring time of 3 min;

[0129] Refining: refining with argon for 10 minutes;

[0130] S2 Casting:

[0131] Casting temperature: 715℃;

[0132] Cooling conditions: soft water cooling, cooling rate 2.8℃ / s;

[0133] Grain refiner: TiB2, added in an amount of 0.02% of the total weight of the melt;

[0134] S3 billet homogenization heat treatment:

[0135] Heat treatment temperature: 480℃;

[0136] Insulation time: 12 hours;

[0137] Cooling method: Furnace cooling to 180℃ and then air cooling;

[0138] S4 Hot Rolled:

[0139] Hot rolling starting temperature: 400℃;

[0140] Single pass reduction rate: 50%;

[0141] Final thickness: 5mm;

[0142] S5 intermediate annealing:

[0143] Temperature: 290℃;

[0144] Insulation time: 2 hours;

[0145] Cooling method: slow cooling;

[0146] S6 Cold Rolled:

[0147] Cold rolling pass reduction rate: 12%;

[0148] Final thickness: 25 μm;

[0149] S7 final annealing:

[0150] Annealing temperature: 230℃;

[0151] Insulation time: 2 hours;

[0152] Cooling method: natural cooling;

[0153] S8 Surface Treatment:

[0154] Cleaning: Soak in 4% nitric acid solution at 40°C for 1 minute, rinse with deionized water for 3 minutes, and dry with hot air;

[0155] Passivation: Use 0.2 mol / L yttrium nitrate solution and soak for 12 minutes at 25°C;

[0156] Rinse: Rinse with deionized water for 3 minutes;

[0157] Drying: hot air drying, temperature 50℃;

[0158] result:

[0159] The conductivity of the aluminum foil prepared was 61% IACS, the tensile strength was 118 MPa, the elongation was 13%, and the corrosion depth was 4.8 μm after being immersed in the electrolyte for 48 hours.

[0160] As a further improvement, the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A production process of rare earth modified aluminum foil for power batteries, characterized in that: The production process comprises the following steps: S1. Smelting: Smelt aluminum ingots at 730-750°C, add rare earth elements and alloy elements silicon, copper, manganese and magnesium to the melt; stir for 3-5 minutes after adding; after smelting, perform argon refining to remove oxides and gas inclusions; S2. Casting: semi-continuous casting or continuous casting and rolling at 710-730°C; controlling the cooling rate to 1.5-3.0°C / s, and controlling the grain size to ≤50μm by using a grain refiner; S3, homogenization heat treatment: the ingot is kept at 450-480℃ for 12-24 hours, furnace cooled to below 200℃ and then air cooled; S4, hot rolling: hot rolling is carried out at 350-450°C, the single-pass reduction rate is 30%-50%, and the final rolling thickness is 5-8mm; S5, intermediate annealing: annealing at 280-320°C for 2-4 hours, followed by slow cooling to room temperature; S6, cold rolling: cold rolling the intermediate annealed plate to a target thickness of 20 to 50 μm, with a cold rolling pass reduction of 10% to 20%; S7, final annealing: annealing at 220-280°C for 2-6 hours to improve material properties; S8. Surface treatment: The surface of the aluminum foil is passivated using a rare earth passivation solution.

2. The production process of a rare earth modified aluminum foil for power batteries according to claim 1, characterized in that: The rare earth element is added in the form of Al-RE master alloy, and the amount of the rare earth element added is 0.05% to 0.3% of the total weight of the melt.

3. The production process of a rare earth modified aluminum foil for power batteries according to claim 2, characterized in that: The rare earth element is one of La, Ce, Nd or Y or a combination of several of them.

4. The production process of a rare earth modified aluminum foil for power batteries according to claim 1, characterized in that: During the smelting process, argon or nitrogen is used for stirring, and the stirring speed is 60 to 100 revolutions per minute.

5. The production process of a rare earth modified aluminum foil for power batteries according to claim 1, characterized in that: The grain refiner is preferably TiB2, and its addition amount is 0.01% to 0.05% of the total weight of the melt.

6. The production process of a rare earth modified aluminum foil for power batteries according to claim 1, characterized in that: The parameters of S8 surface treatment are as follows: Formula of rare earth passivation solution: rare earth salt: 0.1-0.5 mol / L cerium nitrate or lanthanum nitrate or a mixed solution of the two; passivation treatment conditions: temperature: 25-40℃; time: 10-20 minutes; passivation method: immerse the aluminum foil completely in the passivation solution and stir the solution slightly regularly; post-passivation treatment: rinse the surface of the aluminum foil with deionized water for 3-5 minutes to remove the residual passivation solution; dry in hot air or vacuum drying equipment at 50-70℃ to ensure that the passivation film is uniform and stable.

7. The production process of a rare earth modified aluminum foil for power batteries according to claim 6, characterized in that: Maintain microcirculation of the passivation liquid with a flow rate of 0.5 to 1.5 m / s.

8. The aluminum foil prepared by the production process according to claims 1 to 7, characterized in that: The aluminum foil comprises the following chemical components in mass percentage: Si: 0.03% to 0.2%; Cu: 0.01% to 0.1%; Mn: 0.02% to 0.15%; Mg: 0.01% to 0.1%; rare earth elements: 0.05% to 0.3%; the remainder is Al and unavoidable impurities.